An Analysis of Conversational Implicature Found in “Up” Movie - Astria, Rizka; Fitrawati, Fitrawati (Universitas Negeri Padang, 2021)
This research aims to find out the types of Conversational Implicature and types of Maxims that found in movie. This analysis will be based on theory of Coorperative Principle proposed by Paul Grice. The objects of this research is a movie and the script of movie. This study is descriptive qualitative with the analyze the sentence.The result shows that types Conversational Implicature divide into two, Generalized and Particularized Implicature, which dominated is Generalized Conversational Implicature. This type more dominated because it is more effectively used in daily conversation. In daily conversation speaker and listener do not need background knowledge to understand the meaning of utterance. This research also analyze about Maxims, the researcher found types of Maxims, there are, Quantity, Quality, Relation and Manner. Maxim of Quality is more dominated because in daily conversation speaker and hearer needs the truthful information and have evidence.